2019
DOI: 10.1177/1476718x19851538
|View full text |Cite
|
Sign up to set email alerts
|

The screen and the sand-timer: The integration of the interactive whiteboard into an early years free-flow learning environment

Abstract: This article aims to explore how the interactive whiteboard is situated in the social and material conditions of an early years free-flow learning environment. It examines how the affordances of the interactive whiteboard and the expectations of the surrounding classroom impact how activity involving the interactive whiteboard unfolds. It achieves this through an analysis of observations, documented through video, of how children enter into and exit from activities involving the interactive whiteboard during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The present findings also suggest that it is necessary to ensure that children able to achieve positive emotions (Catalano & Campbell, 2021), building a positive self-concept (Aksoy & Baran, 2020), building interaction skills (Aksoy & Baran, 2020;Sakr & Scollan, 2019), and social skills (Aksoy & Baran, 2020;Parrott & Cohen, 2021;Catalano & Campbell, 2021). Through storytelling and drama, children able to express their emotions and build positive self-concept (Halimah et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The present findings also suggest that it is necessary to ensure that children able to achieve positive emotions (Catalano & Campbell, 2021), building a positive self-concept (Aksoy & Baran, 2020), building interaction skills (Aksoy & Baran, 2020;Sakr & Scollan, 2019), and social skills (Aksoy & Baran, 2020;Parrott & Cohen, 2021;Catalano & Campbell, 2021). Through storytelling and drama, children able to express their emotions and build positive self-concept (Halimah et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Social (3 articles) Sakr and Scollan (2019) revealed the diversity in how the children drew the IWB into activity and pointed toward the potential for collaborative creativity in interaction with the IWB. Parrott and Cohen (2021) added that the play was perceived as valuable for helping build friendships and developing social skills, as older children become role models to younger ones.…”
Section: Language (12 Articles)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kirova and Jamison’s (2018) study revealed that many children engaged in meaningful experiences with digital technologies within their home and yet had no independent access to iPads in the classroom. Similarly, Sakr and Scollan (2019) report that ‘studies conducted on digital technologies in early years learning environments present a different story to those conducted in the home’ (p. 191). An example of the distinction between children’s digital technology access and use in the home and early childhood setting is evidenced by the findings of Dashti and Yateem (2018) who revealed that 78% of the children in their study used mobile devices in the home, while only 18% used mobile devices in their early learning setting.…”
Section: Digital Differences Between the Home And Early Childhood Settingmentioning
confidence: 99%
“…Classrooms have particular priorities and practices that influence how resources are taken up. For example, EY learning environments tend to place an emphasis on turn-taking (Sakr, 2017;Sakr & Scollan, 2019). How time is conceptualised and managed in relation to particular semiotic resources is an essential component of the sociocultural context.…”
Section: Time As An Aspect Of the Ey Classroom Contextmentioning
confidence: 99%